EUFEMISME DALAM CERAMAH USTADZ ABDUL SOMAD PADA CHANNEL YOUTUBE USTADZ ABDUL SOMAD OFFICIAL (KAJIAN SEMANTIK) - Ranizah, Ranizah; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This study aims to find out the forms of euphemisms, the benefits of euphemisms in Ustad Abdul Somad's lectures on Ustad Abdul Somad's Youtube Channel and how they are implemented in learning at school. This research uses a descriptive method with a qualitative form. The data collection technique used in this research is using documentary study techniques. This research produced 17 data, 1) 2 data used for abbreviations, 11 data for loan words, 2 data for foreign terms, 2 data for periphrases. Thus the form of euphemism that is more often used by Ustad Abdul Somad in lectures on Ustad Abdul Somad's Youtube Channel is the use of borrowed words. Then 2) for politeness and comfort as much as 6 data, To disguise the meaning as much as 6 data, To reduce embarrassment as much as 4 data, To carry out religious orders as much as 1 data. Thus the benefits of using euphemisms in Ustad Abdul Somad's lectures on the YouTube Channel Ustad Abdul Somad more often use euphemisms to disguise meaning as an effort to be polite in language.